Experimental implementation of a smart battery charger for electric vehicles charging station - Abdelilah Hassoune; Mohamed Khafallah; Abdelouahed Mesbahi; Ayoub Nouaiti; Tarik Bouragba (Institute of Advanced Engineering and Science, 2020)
In this paper, an implementation of a DC/DC buck converter for electric vehicles charging station and a DSP based closed-loop digital controller design are presented and analyzed. The aim of this work is to achieve an improved control strategy for a Li-ion battery charger implemented on a Real-time test platform. The test platform consists of a popular power pole board (MPCA75136) dedicated to studying the DC/DC converters, and a DSP development kit (TMS320F28379D) that is used to drive the DC/DC buck converter. The control strategy is based on a digital control system containing the closed-loop current controller followed by a pulse width modulation block, and on a real time state of charge estimation technique for a Li-ion battery. However, the overall control design is modeled on Simulink via block diagrams, and automatically generated code that is targeted into the DSP processor. Simulation and experimental results have shown the effectiveness of the proposed test bench and its external digital control strategy via a charging scenario for electric vehicles batteries.